Penggunaan Kobalt-Aerosil Komponen Fiberglass Pada Pelapisan Lambung Perahu Nelayan Rumput Laut Dusun Pattontongan Jeneponto - Farianto Fachruddin; Syamul Asri; M. Risal Firmansyah; Wahyuddin Mustafa; Zulkifli Yusuf; Lukman Bochary; Misliah Idrus; Abdul Haris Djalante; Fadhil Riski Clausthaldi (Faculty of Engineering UNHAS, 2021)
Seven sub-districts in Jeneponto Regency are located in coastal areas and are producers of seaweed. Binamu District is the largest producer of seaweed in Jeneponto Regency (14% of total seaweed production). “Cahaya Laut” consists of ten members from a group of fishermen and seaweed farmers in Binamu District, (Pattontongan village). Small boats are the operational means of seaweed cultivation which often experience hull damage due to landings. These boats are generally made of wood or fiberglass. This activity aims to introduce fiberglass material components as reinforcement for the outer layer and function as a substitute for boat hull paint. This component can be a solution to the problem of fishermen/cultivators. The component is cobalt-aerosil or known as HDK (trade namely). This material serves to increase the viscosity and strength of the resin polymer as a fiberglass-forming matrix. The implementation of this service consists of two activities, namely: first, providing counseling and explanations related to the function, purpose, showing the form of Cobalt-Aerosil (HDK) and the theory of its use. Second, materials are implementing on the damaged boat hull as an exercise. From this activity, the participants seemed very enthusiastic and just understood that so far in the use of fiberglass material, they have never used HDK components. From the results of the repair of the boat's hull, it can be seen that they are happy because the hull layer has been colored as desired without needing to be painted and has a fairly high hardness. As a follow-up to this service activity, fishermen/cultivators will repair their boats by using HDK components together with resin and coloration as the hull lining.